European Handbook of Dermatological Treatments - Katsambas, Andreas D.; Katsambas, Andreas D.; Lotti, Torello M.; Lotti, Torello M.; Dessinioti, Clio.; Dessinioti, Clio.; D'Erme, Angelo Massimiliano.; D'Erme, Angelo Massimiliano. (Springer Berlin Heidelberg : Imprint: Springer, 2015)
This guide to dermatological treatments provides concise yet comprehensive, up-to-date overviews of treatment guidelines and pearls for a plethora of skin diseases. It is divided into three main sections that address the many different skin diseases, the drugs available for dermatological treatments, and the various methods applied in dermatology, including fillers, botulinum toxin, lasers, dermoscopy, cryosurgery, and electrosurgery. Each skin disease-focused chapter describes current treatments while also providing a brief synopsis of etiology and clinical presentation. Treatment indications and contraindications, modes of action, and dosages are clearly identified.   This third edition of the European Handbook of Dermatological Treatments has been extensively revised to reflect the advances of the past decade, including biologic agents for psoriasis, also used as promising off-label treatments in other skin diseases, targeted agents for malignant melanoma and basal cell carcinoma, and new treatment modalities for rosacea, acne, atopic dermatitis, and urticaria, to name but a few. The successful easy-to-use format is retained in this new edition, which is enriched with clinical photos that will make reading a pleasurable as well as a learning experience.